Analysis of Mixed Marriage Law in Indonesia From the Perspective of International Civil Law Improvement - Sari, Siti Julaeha Puspika; Setiawan, Andre; Adillah, Alya Sophia; Mustapid, Hidayatul; Khairunnida, Tasya; Wijaya, Mustika Mega (Activa Yuris: Jurnal Hukum, 2025)
Law Number 1 of 1974 concerning Marriage contains a section on religiosity. A man and a woman become husband and wife with the aim of realizing a happy and eternal family based on the One Almighty God. This is the definition of marriage itself. The Civil Code and the Marriage Law have different definitions of marriage: in Article 26 of the Law "The Law views the issue of marriage only in civil relations". The research method used in this study is descriptive normative legal research. With the technique of statutory regulations, as well as other related documents that are related to science, the development of its theory. Primary legal materials are obtained from Law Number 1 of 1974 concerning marriage, while secondary legal materials, namely the Civil Code, textbooks, legal journals, expert opinions and legal experts. The data obtained are both secondary and primary. Because there are foreign components in legal relations, international civil law applies. Algemene Bepalingen are general regulations that regulate international civil norms in Indonesia. In the concept of international civil law, there are 2 types of schools, namely: 1) Internationality which requires international or multilateral civil law. 2) Nationality because each country has different procedures for International Civil Law for Inter-National Marriage. Marriage between two people from different countries is defined as a mixed marriage based on Article 57 of the Indonesian International Civil Law Marriage Law. However, the third factor, not differences in religion, ethnicity, or social class in Indonesia, is the cause of this gap.